Penerapan Smart Tourism sebagai Strategi Transformasi Digital untuk Menarik Wisatawan di Kabupaten Samosir - Aisyah Sihombing; Ika Sartika (Lembaga Pengembangan Kinerja Dosen, 2025)
The research aims to analyze the application of smart tourism as a digital transformation strategy to attract tourists in samosir districts. Using a mix mix approach (qualitative and quantitative), the study examined three key aspects: (1) the application of smart tourism in support of the digital transformation of the tourism sector, (2) the motivations, perceptions, and preferences of tourists, and (3) the contributing factors and implementation barriers. Research shows that web-based digital strategies, samosir tourism applications, and social media have been able to increase tourist attractiveness, with 89.8% of those who rely on digital technology for travel planning. However, challenges such as unequal digital infrastructure and low local UMKM participation on digital platforms are still a hindrance. USES and drivers theory are used to understand how tourists actively use digital technology. The study concludes that smart tourism does have a significant impact on the increase in tourist visits, while also offering recommendations for expanding Internet networks, leveraging apps, and empowering local businesses through digital training. These findings favor samosir districts as a continuing modern tourist destination.